An investigation into the effect of a pre-performance strategy on jump performance - Fletcher, I. M. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to explore the effect that different components, making up a commonly used pre-performance preparation strategy, have on jump height performance. Sixteen male collegiate athletes (age, 21.38 ± 0.52 years; height, 1.79 ± 0.07 m; and body mass, 75.1 ± 5.26 kg) performed a preparation strategy involving a cycle ergometer warm-up, followed by a dynamic stretch component, and finishing with heavy back squats. This intervention was repeated to test countermovement, squat or drop jump performance after each component of the preparation strategy, with electromyographic activity measured during each jump test. Significant increases (p < 0.05) in jump height and electromyographic activity were noted, with a stepwise increase in performance from pre- to post-warm-up, increased further by the dynamic stretch component and again increased after the back squat. It was also noted that the increases in performance, attributed to the stretch and lift components, were significantly greater (p < 0.05) than the increases in jump height associated with the active warm-up. It seems likely that the initial active warm-up raised core temperature, helping to increase the jump performance. The specific movements employed in the stretch and lift interventions seemed to potentiate the agonistic muscles involved in jumping, shown by increases in electromyographic activity in the prime movers for the jumps explored. This could be an example of postactivation potentiation, where muscles are primed to increase performance beyond changes linked to an active warm-up.